Influence of dimethyl dicarbonate on the resistance of Escherichia coli to a combined UV-Heat treatment in apple juice - Gouma, Maria; Gayán, Elisa; Raso, Javier; Condón, Santiago; Álvarez, Ignacio (Frontiers in Microbiology, 2015)
Commercial apple juice inoculated with Escherichia coli was treated with UV-C, heat (55°C) and Dimethyl Dicarbonate - DMDC (25, 50 and 75 mg/L)-, applied separately and in combination, in order to investigate the possibility of synergistic lethal effects. The inactivation levels resulting from each treatment applied individually for a maximum treatment time of 3.58 min were limited, reaching 1.2, 2.9 and 0.06 Log10 reductions for UV, heat and DMDC (75 mg/L), respectively. However, all the investigated combinations resulted in a synergistic lethal effect, reducing the total treatment time and UV dose, with the synergistic lethal effect being higher when larger concentrations of DMDC were added to the apple juice. The addition of 75 mg/L of DMDC prior to the combined UV-C light treatment at 55°C resulted in 5 Log10 reductions after only 1.8 min, reducing the treatment time and UV dose of the combined UV-Heat treatment by 44%.